2004
DOI: 10.1007/s00213-004-1993-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive effects of methylphenidate in adult attention-deficit/hyperactivity disorder

Abstract: Adults with ADHD had a similar neurocognitive response to methylphenidate to that previously reported for childhood ADHD. Our results provide further support for the validity of the ADHD syndrome as defined by DSM-IV and indicate possible neurocognitive substrates for clinical improvement with chronic methylphenidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 80 publications
2
66
3
Order By: Relevance
“…With regard to prospective memory, a difference between patient groups of medium size was only revealed by the planning task, supporting the notion that in particular measures related to attention/executive functions are sensitive to the effects of MPH on cognition of patients with ADHD. This notion is also supported by findings of previous research showing that pharmacological treatment with MPH resulted in substantial improvements of attention and planning skills of adults with ADHD (Coghill et al, 2013;Tucha, Prell, et al, 2006;Turner et al, 2005). It still remains unsolved why considerably smaller effects were found on measures of memory as compared to measures of attention/executive functions.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…With regard to prospective memory, a difference between patient groups of medium size was only revealed by the planning task, supporting the notion that in particular measures related to attention/executive functions are sensitive to the effects of MPH on cognition of patients with ADHD. This notion is also supported by findings of previous research showing that pharmacological treatment with MPH resulted in substantial improvements of attention and planning skills of adults with ADHD (Coghill et al, 2013;Tucha, Prell, et al, 2006;Turner et al, 2005). It still remains unsolved why considerably smaller effects were found on measures of memory as compared to measures of attention/executive functions.…”
Section: Discussionsupporting
confidence: 66%
“…A large number of studies on adults with ADHD reported positive effects of MPH on several aspects of cognition, including alertness, vigilance, selective attention, divided attention, working memory, response inhibition, and flexibility (Aron, Dowson, Sahakian, & Robbins, 2003;Coghill et al, 2013;O. Tucha, Mecklinger et al, 2006, L. Tucha et al, 2011Turner, Blackwell, Dowson, McLean, & Sahakian, 2005). However, considerably less evidence exists presenting the effects of MPH on memory functions of adults with ADHD.…”
mentioning
confidence: 99%
“…Consistent with this, drugs used to treat ADHD, including psychostimulants, SNRIs and a 2 -receptor agonists, improve an array of PFCdependent processes (Chamberlain et al, 2007;Diamond, 2005;Mehta et al, 2001;Turner et al, 2005). Neurochemically, low and clinically relevant doses of MPH preferentially increase extracellular levels of NE and DA within the PFC relative to other cortical and subcortical regions (for review, Berridge and Devilbiss, 2011).…”
Section: The Pharmacology Of Adhd: Preferential Targeting Of the Pfcmentioning
confidence: 96%
“…Although psychostimulant medications have been shown to improve working memory (Turner, Blackwell, Dowson, McLean, & Sahakian, 2005), medical treatments for ADHD may cause negative side effects and can lead to prescription medication abuse (Advokat, 2010;DavisBerman & Pestello, 2010;Janusis & Weyandt, 2010). Furthermore, improvements in working memory associated with medications are likely to depend on medication levels, disappearing when medication levels drop between doses.…”
mentioning
confidence: 99%